Immediate postpartum intrauterine contraceptive device utilization and influencing factors in Addis Ababa public hospitals: a cross-sectional study - Yohannes Fikadu Geda; Seid Mohammed Nejaga; Mesfin Abebe Belete; Semarya Berhe Lemlem; Addishiwet Fantahun Adamu (BMC, 2021)
Abstract Background Postpartum intrauterine device (PPIUCD) utilization remains very low in Ethiopia beside high levels of unmet need for postpartum family planning even if nongovernmental organizations efforts to promote its use. This study investigates immediate PPIUCD utilization and influencing factors. Methods Institution based cross-sectional study was conducted on public hospitals of Addis Ababa city. All public hospitals which have PPIUCD service were included and systematic random sampling technique was used to select 286 participants. Data were entered using Epi Data and exported to SPSS for analysis. Bivariate and multivariate logistic regression analysis was used to determine the effect of independent variables on immediate PPIUCD utilization. Variables which have P-value< 0.2 on bivariate analysis were candidate for multivariate analysis. Variables which have P-value ≤0.05 on multivariate analysis was considered as statistically significant. Results Utilization of immediate PPIUCD among participants who gave birth in Addis Ababa public hospitals was 26.6% (95%CI: 21.3, 31.8). Eighty one percent respondents occupation was housewife were (AOR = 0.19, 95%CI: 0.06, 0.67) less likely to utilize PPIUCD compared to those who have personal job. In the other hand respondents who have discuss about PPFP with their partner were 1.21times (AOR = 1.21, 95%CI: 1.14, 25.67) more likely to utilize PPIUCD compared to those who never discuss. Contrarily 81% of respondents who need partner approval were (AOR = 0.19, 95%CI: 0.05, 0.79) less likely to utilize PPIUCD compared to those who doesn't need approval. Respondents who have been counseled about PPIUCD were 1.13 times (AOR = 1.13, 95%CI: 1.10, 2.21) more likely to utilize PPIUCD compared to those who were not counseled. Similarly respondents who have good knowledge about PPIUCD were 7.50 times (AOR = 7.50, 95%CI: 4.06, 9.31) more likely to utilize PPIUCD compared to those who have poor knowledge. Conclusion This study verifies that immediate PPIUCD utilization is high compared to other studies. Having a housewife occupation and necessity of partner approval to utilize PPIUCD have negative influences, whereas spousal discussion about PPIUCD, counseled during pregnancy and having good knowledge have positive influences on PPIUCD utilization. Therefor empowering women by the government and other organizations working on maternal health will advance immediate PPIUCD utilization.